Water—air gas exchange of elemental mercury: An experimentally determined mercury diffusion coefficient for Hg0 water—air flux calculations. (20th July 2014) - Kuss, Joachim
Abstract : The evasion of elemental mercury (Hg 0 ) from water surfaces is a key process in biogeochemical mercury cycling. Knowledge of the Hg 0 diffusion coefficient ( D HG0 ) in water is essential for Hg 0 water—air flux calculations, but no measured value has been available. In this study, D HG0 was measured in pure water and in water of oceanic salinity within an environmental temperature range between 5°C and 30°C. A diffusion cell was constructed consisting of two chambers separated by an aqueous gel membrane allowing molecular diffusion only. The corresponding parameterizations were developed on the basis of the Eyring equation, which defines an activation energy ( E a ) for the diffusion process. The temperature dependences of D HG0 (in cm 2  s −1 ) for freshwater, D fresh HG0 = 0.0335 e −(18.63 kJ mol−1)/ RT, and for seawater, D sea HG0 = 0.0011 e −(11.06 kJ mol−1)/ RT, with R the gas constant and T the temperature in Kelvin, were thus obtained with an error of ±15%. Whereas the measured D fresh HG0 was in good agreement with the theoretical proposals of a molecular dynamics (MD) simulation, D sea HG0 was clearly lower, probably because of the unaccounted effect of the polarization of mercury atoms in the salt solution, which hampers diffusion. In geochemistry applications, use of the newly determined D sea HG0 instead of the D HG0 from MD simulations would have differential effects on determinations of mercury emissions from the world's oceans. The effect on the tropical ocean would be the largest, decreasing the Hg 0 water—air flux estimate by 20%. Toward higher latitudes (∼50°), the calculated emission would drop by about 10%. On the basis of a recent large data set, the estimated amount of mercury released by the Atlantic Ocean would decrease by approximately 17%.